2017
DOI: 10.1007/s12602-017-9342-2
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antimicrobial Activity and Downregulation of Virulence Gene Expression on Helicobacter pylori by Reuterin

Abstract: Helicobacter pylori is an infectious agent commonly associated with gastrointestinal diseases. The use of probiotics to treat this infection has been documented, however, their potential antimicrobial metabolites have not yet been investigated. In the present study, the effect of reuterin produced by Lactobacillus reuteri on H. pylori growth and virulence gene expression was evaluated. It was observed that reuterin caused significant (P < 0.05) H. pylori growth inhibition at concentrations from 0.08 to 20.48 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 39 publications
1
31
0
2
Order By: Relevance
“…Activation of H. pylori was performed in 5 mL of trypticase soy broth (TSB; Becton Dickinson, Franklin Lakes, NJ), supplemented with 5% (v/v) heat inactivated fetal bovine serum (FBS; Gibco, Gaithersburg, MD). A er, 50 μL of bacterial suspension was plated on trypticase soy agar (TSA; Becton Dickinson), supplemented with 5% (v/v) de brinated sheep blood (DSB), as reported by Urrutia-Baca et al [32]. Broth and agar cultures were placed into a sealed jar with CampyGen sachet (Oxoid Ltd, Basingstoke, UK) to maintain microaerobic conditions and incubated at 37°C for seven days.…”
Section: Methodsmentioning
confidence: 99%
“…Activation of H. pylori was performed in 5 mL of trypticase soy broth (TSB; Becton Dickinson, Franklin Lakes, NJ), supplemented with 5% (v/v) heat inactivated fetal bovine serum (FBS; Gibco, Gaithersburg, MD). A er, 50 μL of bacterial suspension was plated on trypticase soy agar (TSA; Becton Dickinson), supplemented with 5% (v/v) de brinated sheep blood (DSB), as reported by Urrutia-Baca et al [32]. Broth and agar cultures were placed into a sealed jar with CampyGen sachet (Oxoid Ltd, Basingstoke, UK) to maintain microaerobic conditions and incubated at 37°C for seven days.…”
Section: Methodsmentioning
confidence: 99%
“…Probiotic supplementation is an emerging field in H. pylori treatment (Chey et al 2017). In vitro studies report inhibitory effects of probiotics on the expression level of genes encoding virulence factors, including ureB, vacA, flaA, and sabA (Lesbros-Pantoflickova et al 2007;de Klerk et al 2016;Urrutia-Baca et al 2018). Some probiotics, such as Lactococcus lactis, Lactobacillus reuteri, and Lactobacillus bulgaricus produce peptide and nonpeptide antipathogen substances that can inhibit the growth, as well as the adhesion process, of H. pylori (Kim et al 2003;Boyanova et al 2017;Urrutia-Baca et al 2018).…”
Section: Probiotics In the Treatment Of H Pylorimentioning
confidence: 99%
“…Boyanova et al found that the bacteriocin secreted by seven L. bulgaricus strains not only inhibited the growth of antibiotic-sensitive H. pylori strains, but also the antibiotic-resistant strains [72]. In addition to these peptide-like bacteriocins, a nonpeptide antipathogen substance synthesized by L. reuteri, called reuterin, can inhibit H. pylori growth and downregulate the expression of the virulence genes vacA and flaA [73].…”
Section: Antagonistic Mechanismmentioning
confidence: 99%